Appropriate breeding strategies for small ruminant production in West and Central Africa - Osinowo, O.A.; Abubakar, B.Y. (1989)
Small ruminant production is widespread throughout all the ecological zones of West and Central Africa. The seasonal climate of the area influences growth and reproduction of the animals through its effects on forage availability and disease prevalence. Distribution of the breeds show evidence of ecological adaptation, the dwarf, trypanotolerant breeds being predominant in the humid areas while the larger, long-Iegged breeds predominate in the drier areas. There exist at least 11 sheep and 4 goat breeds indigenous to the regions but many are still poorly characterized. There is a great need for the standardization of breed names across national boundaries. Large gaps still exist in the available performance data for most of the breeds. Generally however, their reproductive rates are fairly high while growth rates and milk yields are low. Genetic improvement should be focussed on growth and reproductive traits. I for breed improvement on a national or regional scale, an open nucleus breeding scheme is recommended, involving central nucleus, multiplier and farmers flocks. Such a scheme should be backed by an effective extension service for maximum effect.